Hubungan Status Gizi dengan Tingkat Kebugaran Jasmani pada Driver Ojek Online di Kota Denpasar - Yudhi Pratama; Ni Ketut Sutiari (Poltekkes Kemenkes Mataram, 2020)
Online ojek driver is in a risk of having less healthy and overweight body for their busy working activities as well as high riding mobility causing limited until no chance to do exercise. Physical fitness is affected by some factors which are age, sex, smoking habit, health status and physical activity. Besides, the physical fitness is also provoked by nutritional status. If someone has poor health status, it will decrease the physical fitness level and give impact to the ojek driver productivity also make the work feel exhausting. This research is aimed at understanding the relationship between nutritional status and the physical fitness of online ojek driver in Denpasar. This research is analytic cross-sectional study. The sample amounts 60 male. The sample was chosen by using accidental sampling in 4 sub-districs in Denpasar. The result showed that 61.7% of online ojek driver are overweight based on body mass index (BMI) and abdominal circumference >90 centimeters is 41.7%. Online ojek drivers in Denpasar 55.0% are not fit. The statistic result showed that BMI (p=0.000) and abdominal circumference (p=0.000). Conclusion on this research is nutritional status are related to the physical fitness level of the online ojek driver.